2019
DOI: 10.1007/s13201-019-1114-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequestered capture and desorption of hexavalent chromium from solution and textile wastewater onto low cost Heinsia crinita seed coat biomass

Abstract: Due to the high cost associated with the treatment of effluents containing heavy metals in the environment, the continuous untreated release of effluent containing chromium from textile industries has resulted in several adverse effects to plants, ecological systems and humans. This research therefore focused on the use of a low cost, biodegradable Heinsia crinita seed coat (HCSC) material for the biosorption of chromium(VI) from aqueous and textile contaminated effluent. The biosorbent was characterized for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…The slopes obtained are close to 1 which showed that the extract adsorption on the metal was monolayer adsorption and that no interaction existed between extract and mild steel (Ashassi-Sorkhabi et al 2004;Ebenso et al 2008;Dawodu et al 2020;Kamga 2019).…”
Section: Adsorption Considerationsmentioning
confidence: 68%
“…The slopes obtained are close to 1 which showed that the extract adsorption on the metal was monolayer adsorption and that no interaction existed between extract and mild steel (Ashassi-Sorkhabi et al 2004;Ebenso et al 2008;Dawodu et al 2020;Kamga 2019).…”
Section: Adsorption Considerationsmentioning
confidence: 68%
“…Adsorption thermodynamics analysis was performed to evaluate the enthalpy change (ΔH°), entropy change (ΔS°) and Gibbs free energy change (ΔG°) by the application of the given equations 62 :…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…Adsorption thermodynamics analysis was performed to evaluate the enthalpy change (ΔH°), entropy change (ΔS°) and Gibbs free energy change (ΔG°) by the application of the given equations 62 : where symbols R (J/mol K), T (K) and K c correspond to the ideal gas constant, absolute temperature and distribution coefficient respectively.…”
Section: Thermodynamic Analysismentioning
confidence: 99%
“…During the first cycle, the desorption yields achieved were 7.10 and 83.13% for nickel and lead ions, respectively. As the number of cycles increased, the desorption yields reduced, which can be attributed to damage in biomass structure after using desorbing agents [ 34 ].…”
Section: Resultsmentioning
confidence: 99%